Blockchain in healthcare - Yee, Lina Li Ting (2019)
Blockchain technology works on a decentralized network and provides a secure and trust-less system where privacy can be ensured without authority or institutional intervention. In the healthcare industry, large amount of sensitive data is being transacted, both handwritten and electronically. The blockchain would greatly benefit the healthcare industry by enabling traceability and integrity of data. Patients will be able to have better control of their healthcare information. This project starts with a background studies on the blockchain technology, then it reviews the security issues faced in the storing of medical records in the healthcare industry. After which it discusses a use case that can increase data integrity and give patients better control of their personal information. Then, a blockchain application is developed based on the concept of the use case to demonstrate the feasibility of a Blockchain in Healthcare application.